Integrated valorization of waste cooking oil and spent coffee grounds for biodiesel production: Blending with higher alcohols, FT–IR, TGA, DSC and NMR characterizations. (15th May 2019) - Atabani, A.E.; Shobana, Sutha; Mohammed, M.N.; Uğuz, Gediz; Kumar, Gopalakrishnan; Arvindnarayan, Sundaram; Aslam, Muhammad; Al-Muhtaseb, Ala'a H.
Graphical abstract: Highlights: Spent coffee grounds extracted oil (SCGO) to biodiesel conversion demonstrated. Binary blend of waste cooking oil (WCO) and SCGO (50/50% by volume) used. Blending with higher alcohols improves density and cold flow properties. Blended-Biodiesel exhibits excellent cetane number of 56.4. Abstract: This work deals for the first time with recycling a binary blend of waste cooking oil (WCO) and spent coffee grounds oil (SCGO) (50/50% by volume) into biodiesel. Additionally, this work aimed at valorizing both wastes while improving fatty acids composition to obtain a stabilized product due to low degree of unsaturation of SCGO besides, reducing its high acid value. Furthermore, blending with Euro diesel and higher alcohols of butanol, pentanol and hexanol to improve some biodiesel properties was investigated. Furthermore, FT–IR, UV– vis ., TGA, DSC and NMR analyses to assess the blends quality was examined. Results have proved the advantage of pre-blending and higher alcohols addition to improve the fuel properties. The biodiesel exhibits excellent cetane number of 56.64, oxidation stability of about 6.51 h and iodine value of 83.71 (g iodine/100 g) due to the low degree of unsaturation (89.02). Blending with higher alcohols improves density and cold flow properties while keeping acceptable level of cetane number, flash point and higher heating value (HHV) rather than lower alcohols. Consequently, this opens new gates for biodiesel research area. In conclusion, this work reinforces that blending of WCO and SCGO improves biodiesel properties and add to the economy of this industry. Therefore, further examination on the blends effect in compression ignition diesel engines through engine emissions and combustion characteristics is recommended.